UNDERSTANDING INSULIN RESISTANCE IN NIGERIAN TYPE 2 DIABETES CASES - Anaja, Amina (Ayden Journal of Drug and Pharmaceutical Research, 2024)
Diabetes mellitus (DM) has become a global public health concern, reaching regions previously considered unaffected, such as rural Africa. The prevalence of DM is increasing worldwide, especially in developing areas due to factors like population aging and urbanization. Current projections indicate a significant rise in the number of people affected by DM, with estimates suggesting a 54% increase in the global adult diabetic population from 2010 to 2030. DM comprises a group of metabolic disorders characterized by elevated blood glucose levels, resulting from insufficient insulin production or the body's decreased response to insulin. The classic symptoms of DM include frequent urination, increased thirst, and heightened hunger, which are all consequences of disrupted fluid and energy metabolism. The most common form of DM is type 2 diabetes, primarily characterized by insulin resistance and, to some extent, reduced insulin secretion